Schistosomiasis and Recurrent Arthritis: A Systematic Review of the Literature - Coline Mortier; Maïssane Mehadji; Sophie Amrane; Anne-Laurence Demoux; Coralie L’Ollivier (Pathogens, 2022)
Background. Schistosomiasis is an endemic parasitic infection found in many tropical countries and is highly prevalent in sub-Saharan Africa. It can follow different and atypical clinical patterns. In these unusual cases, diagnosis may be difficult, as symptoms are unspecific. Arthropathy can appear in parasitic infections, but making a connection between arthritis and parasitic aetiology is difficult. This review aims to summarise all cases that have reported schistosomiasis associated with arthropathy, and the different ways authors have diagnosed this disease. Method. We present a systematic literature review of schistosomiasis associated with joint impairments, with a focus on the difficulty of differentiating between reactive arthritis and its parasitic presence in situ. Results. Joint impairments mimicking polyarthropathy are not rare in parasitic infections. Diagnosis is difficult. On the one hand, some patients have arthritis with parasite eggs found in situ, particularly in synovial biopsy. These situations are less common and antiparasitic treatment is straightforward. On the other hand, arthritis can be associated with parasitic infections in the form of reactive arthritis due to an immunological reaction. In such cases, pathogenicity due to circulating immune complex should be suspected. Anti-inflammatory treatments such as corticosteroids or immunosuppressive therapies are ineffective in cases of schistosomal arthropathy. A joint fluid puncture appears to be necessary and parasitic examination as well as in situ immunological techniques appear to be important in order to confirm the diagnosis of schistosomal arthropathy. Conclusions. The frequency of articular schistosomiasis is probably underestimated and should be sought when patients have unexplained polyarthropathy, as it can be an alternative diagnosis when patients have concomitant parasitic infections. These situations are common, whereas the association between unexplained inflammatory arthritis and a concomitant parasitic infection is rarely made. Unspecific rheumatism can lead to probabilistic treatments with many side effects, and looking for a parasitic aetiology could lead to repeated antiparasitic treatments and may avoid other immunosuppressive or corticosteroid therapies. With increasing travel and global migration, physicians need to be more aware of nonspecific symptoms that may reveal an atypical presentation of a tropical disease that can be treated easily, thus avoiding inappropriate immunosuppressive treatments.